Autopilot telemetry and data structure sub-system development - Lim, Raphael De Sheng (2014)
Developing of telemetry system to ensure communication between ground control station and plane wirelessly based on MAVLink Protocol. To ensure data is robust and efficient by adopting suitable data structure.